Pengembangan Aplikasi Sistem Informasi Akademik Berbasis Web Menggunakan Framework Laravel: Studi Kasus di SMK Assalam Depok - Nasution, Muhammad Nashir; Maulana, Reza (Jurnal Informatika Terpadu, 2024)
ASSALAM Vocational High School Depok is an educational institution that prepares generations for the world of work. Currently, ASSALAM Vocational High School Depok still uses a manual system in the academic data collection process so that the process takes a long time and is inefficient by having to enter data one by one. Therefore, a system is needed that can manage academic data for ASSALAM Vocational High School Depok. In building the SISKA ASSALAM application, the data collection stage is carried out through observation and interviews with ASSALAM Vocational High School Depok. At the design stage, using the Unified Modeling Language (UML) to design the end user. At the development stage, using the R&D development method. Then, for the testing method on the application, using two methods, namely Black-Box Testing and Usability Testing. Based on the test results using Black-Box Testing, the results were 100%. For testing using Usability Testing by filling out questionnaires from 9 respondents, the results were 96%. These results indicate that the SISKA ASSALAM application that was designed has been in accordance with the needs required by ASSALAM Vocational High School Depok.